Signalome-wide assessment of host cell response to hepatitis C virus - Gholamreza Haqshenas (Nature Portfolio, 2017)
Development of antiviral strategies depends on an understanding of virus–host interactions. Here, using HCV, Haqshenaset al. show that antibody microarray combined with a targeted siRNA screen can be a powerful tool to identify cellular signalling pathways that are important for virus replication.